Servindo ao Santo Ofício entre a norma e o poder : os agentes inquisitoriais (1580-1640) - Ferreira, Débora Cristina dos Santos (2014)
The Tribunal of the Holy Office of the Inquisition was established in Portuguese lands in the year 1536, after a series of negotiations of the King of Portugal, D. John III, with the Holy See, a court royal and ecclesiastical, who used these two swords to wield their power. The institutional structure of the Holy Office received its first charter in 1552, undergoing several changes until the second is drawn up in 1613, the other is written in 1640 and last longer during Pombal in 1774. These regiments had to regulate the practice inquisitorial function, since the procedures and standards for the establishment of an inquisitorial process until issues of maintenance provisionses of all seats of the Court. Also sought to regulate the exercise of the powers of its officers, these were laymen and clerics, acting not only in offices but also overseas, obtaining a post in the Inquisition allowed these men to achieve social prestige and handouts, enacted by monarchs in order to give agents inquisitorial social status. Thus, we believe that the composition of the thinking is inquisitorial also think the networks of negotiations, the spaces of social promotion. We focus our work in the law of the seventeenth century, Regiments 1613 and 1640, which sought to regulate the practice inquisitorial in each of their offices, and they Lisbon, Evora, Coimbra and Goa. To dwell on these sources seek glances about the discrepancy between them, the innovations and new practices put in Regiments, the growing process of bureaucratization of the institution and its body agents. And understand the positions of power of its agents within the social fabric.